2020
DOI: 10.1136/annrheumdis-2020-eular.6097
|View full text |Cite
|
Sign up to set email alerts
|

Ab1339-Hpr safety and Adherence of the Jak Inhibitors in Clinical Practice in Rheumatoid Arthritis

Abstract: Background:The Janus Kinase (JAKi) inhibitors Baricitinib (BAR) and Tofacitinib (TOF) are indicated for moderate to severe active rheumatoid arthritis (RA). Data about safety, effectiveness in refractory patients and adherence in real clinical practice in our population are scarce.Objectives:An evaluation of safety, adherence and reasons to consider suspension of JAKi in routine clinical practice.Methods:Retrospective observational study of patients with RA treated with BAR and TOF according to usual clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Persistence of treatment was reported in three studies, with a treatment time of 7.6 months (mean) (43), 8.9 months (SD: 5.1 months) (47), 13.2 months (median) (46), respectively. One study also compared the persistence between patients receiving tofacitinib in monotherapy (9/23, 39.1%) versus in combination with csDMARD (26/43, 60.5%) (49).…”
Section: Baseline Disease Characteristicsmentioning
confidence: 98%
See 4 more Smart Citations
“…Persistence of treatment was reported in three studies, with a treatment time of 7.6 months (mean) (43), 8.9 months (SD: 5.1 months) (47), 13.2 months (median) (46), respectively. One study also compared the persistence between patients receiving tofacitinib in monotherapy (9/23, 39.1%) versus in combination with csDMARD (26/43, 60.5%) (49).…”
Section: Baseline Disease Characteristicsmentioning
confidence: 98%
“…Related to the occurrence of AEs, studies reported the percentage of AEs as between 15.0% (6/40) (39) and 39.0% (11/28) (43). The most frequent AEs in each study included: infections (68/122, 55.7%) (53), hypercholesterolemia (5/9, 55.5%) (46), and herpes zoster (HZ), with the latter being the most repeated AE throughout the studies, representing between 3.3% (4/122) (53) and 30.8% (4/13) of cases (47). Infections reported in several of the studies were respiratory infections 33.3% (2/6), odontogenic infections 16.7% (1/6) (39) and infections in general 69.7% (46/66).…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations